Ion acceleration from aluminium plasma generated by a femtosecond laser in different conditions. Issue 4 (5th February 2020) - Torrisi, Lorenzo; Rosinski, Marcin; Terwinska, Dominika; Tchorz, Przemyslaw; Cutroneo, Mariapompea; Torrisi, Alfio
Abstract: Non‐equilibrium plasma was obtained by irradiating Al foils in vacuum with a femtosecond (fs) laser at intensities of the order of 10 18  W/cm 2 . Protons and other light ions were accelerated in the forward direction by using the target‐normal‐sheath acceleration regime. Time‐of‐flight technique was employed to measure the ions' kinetic energy using SiC detectors placed at known distances and angles. The ion acceleration was monitored under different conditions of laser focal position, laser pulse energy, and laser contrast. The target was irradiated using different thicknesses and anti‐reflecting graphene films. By optimizing the laser parameters, irradiation conditions, and target properties, it was possible to accelerate up to 2.3 MeV per charge state, as will be presented and discussed.